Online Collaboration and Self-Regulated Learning in Online Learning Environment: Farhana Khurshid (PJDOL, 2023)
This intervention study explored the development of self-regulated learning skills in virtual university students, focusing specifically on an online collaborative group project with a wiki. Participants of the study were male and female students (n=28) on a Master of Business Management (MBA) Programme of the university. Students participated in an online collaborative group project though wiki for 10 weeks during one semester. Students’ self-regulated learning (SRL) skills were assessed through MSLQ (Motivated Strategies for Learning Questionnaire), developed by Pintrich, Smith, Garcia, & McKeachie (1993). M